The Importance of Practical Issues in the Development of Professional Competence of Students of Technical Higher Education Institutions - Fayzullaev Jamshid Ismoiljonovich (Genius Journals, 2022)
This article reveals the purpose of developing students' professional competence based on a problem-based approach in solving and analyzing scientific, technical and professional problems that arise in the process of teaching students of technical higher education institutions to ensure and control the quality of education
Keywords: Education; activity; problem; competence